Peranan Agama dalam Pengembangan Masyarakat - Derry Ahmad Rizal; Moh. Syaiful Bahri (Da'wa Faculty IAIN Purwokerto, 2021)
Community development becomes an interesting research field to study, this is due to the increasing variety in community development. Without focusing on natural resources (SDA) owned, creative communities in pouring ideas to develop. Guided by creativity and community has the desire to build a village, this becomes the main value that must be applied. But this study will present an understanding of how religion and society have a close relationship, not in terms of routine worship practices. The application of religious values in social life, specifically regarding the development of society. The approach in this study uses the study of literature or literature from various references obtained. It does not justify any understanding, but that the development of a society based on religious values and the development of a special Islamic society also has its own advantages, this goes back to the decisions of the community itself in practice.